Strategi Komunikasi dalam Konten Edukasi Teknologi pada Kanal Youtube: Gadgetin (Mei 2024) - Arjun Naja; Mukhlis Mukhlis; Murywantobroto Murywantobroto (Journal on Education, 2024)
This study examines the communication strategies employed by GadgetIn, a prominent Indonesian technology education YouTube channel, during May 2024. As digital platforms become increasingly important for technology education, understanding effective communication strategies is crucial for delivering complex technical information to general audiences. The research analyzes eight videos published by GadgetIn in May 2024, employing observational and documentation methods to examine content delivery, visual presentation, and audience engagement strategies. The study reveals that GadgetIn successfully maintains viewer engagement through consistent informal yet informative presentation styles, averaging over 1 million views per video. Key findings demonstrate the channel's effective use of multimedia elements, including infographics, product comparisons, and split-screen demonstrations, while maintaining a balance between technical accuracy and accessible presentation. The research concludes that GadgetIn's success in technology education stems from their ability to combine accurate information with engaging delivery methods, creating an effective model for digital technology education. Their approach reflects a deep understanding of audience preferences and modern content consumption patterns, successfully simplifying complex technological concepts for general viewers while maintaining content credibility and entertainment value.